Robotic‐assisted laparoscopic removal of dermoid cyst mimicking an enlarged cystic mass in the seminal vesicle. Issue 5 (29th June 2022) - Lascano, Danny; Hsieh, Kelly; Kedia, Bhuvi; Higgins, John P; Chung, Benjamin I
Abstract : Introduction: Isolated seminal vesicle cysts not associated with Zinner syndrome is a rare disorder that can present initially with urinary obstructive symptoms or nonspecific groin pain. Case description: We present the uncommon case of a dermoid cyst mimicking a seminal vesicle cyst treated with robotic‐assisted laparoscopic seminal vesiculectomy. Conclusion: For dermoid cysts, surgical excision is the gold standard of treatment with a high cure rate and little risk of regrowth if spillage is avoided and full resection is completed. Robotic‐assisted laparoscopic surgery is a viable management option with good visualization of the anatomy.